How Do Determiners of Job Performance Matter During COVID-19? The Conservation of Resource Theory - Zhao, Wen-Xuan; Shao, Lijin; Zhan, Mingjun; Peng, Michael Yao-Ping (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, business managers are facing many challenges from a severe challenge. Many organizations have changed their original management mode and organizational behavior to improve employees' organizational citizenship behavior, thus reducing their sense of anxiety and incapability. Thereinto, job performance of the employees also affects the growth and development of the organization. To explore how to fragment employees' positive psychology and job performance, this study discusses the influence on employees' subjective well-being and job performance from relevant factors at the organizational and individual levels. Also, to explore the influence of organizational support and occupation self-efficacy on job performance and the mediating role of subjective well-being during COVID-19, a total of 618 valid questionnaires were collected from all walks of life in 2020. Hypotheses were tested by structural equation modeling and Bootstrap technology. The results show that: (1) Professional self-efficacy and subjective well-being have a significant positive impact on job performance; (2) Subjective well-being plays a complete mediating role between organizational support and job performance, and subjective well-being plays a partial mediating role between professional self-efficacy and job performance; (3) Compared with the sense of organizational support, the positive effect of self-efficacy on job performance is more significant.